BCD spectrophotometry of stars with the B[e] phenomenon : I. Fundamental Parameters - Cidale, Lydia Sonia (2001)
Low resolution spectra in the λλ3500-4600 Å wavelength range of 23 stars with the B[e] phenomenon are presented. Spectral classification of 15 program stars was performed using the BCD spectrophotometric system, based on the study of the Balmer discontinuity, which is independent of interstellar and circumstellar dust extinctions and of circumstellar gas emissions and/or absorptions. From calibrations of the BCD parameters we determined the of the studied stars. For stars where this method could not be applied, we tried to estimate the temperature of the central star by using the Balmer and He I emission lines and/or their visible energy distribution. The colour temperature and the temperatures obtained from the study of Balmer and He I lines are consistent with each other. The new results are compared with those obtained previously by other authors and discussed for each star individually. For some stars, differences between the effective temperatures derived using the BCD classification system and those obtained elsewhere, based on photometric or spectroscopic analysis, imply spectral-type classification disagreements ranging from 2-3 up to 6 B sub-spectral types. The fundamental parameters of AS 119, CD-245721, Hen2-91, HD 316375 and BD-114747 were determined for the first time. A simple method was introduced to calculate total (interstellar+circumstellar) dust extinction towards the studied stars. For HD 53179, which is a double stellar system, and for HD 45677 and HD 50138, which are suspected to be binaries, we predicted the characteristics of the components that are consistent with the observed parameters. However, the possible binarity of HD 45677 and HD 50138 still needs to be confirmed spectroscopically.